ANALYSIS OF THE CAUSES OF DEFECTS IN THE MANUFACTURE PROCESS IMPROVING PRODUCTION QUALITY IN PIRN WINDER MACHINE BY USING STATISTICAL PROCESS CONTROL (SPC) METHOD AT PT. XYZ MAJALENGKA - Indra Permana, Satrio; Whydiantoro; Rizanuddin N, Hafni; Budiman; Kusumadewi, Intan (Jurnal Mekanika dan Manufaktur, 2023)
In manufacturing companies, production activities are a very important activity. If the production activities produce a lot of defective products, it will cause losses in the form of additional time and raw material costs for repairing these defective products, so that quality control is needed so that the company can produce products that comply with predetermined quality standards. This final project research was conducted at PT. XYZ Majalengka where this company is engaged in the service industry, production activities at PT. XYZ Majalengka is carried out based on a make to order response demand strategy, namely the company carries out production activities when there are orders from consumers. This research focuses on the production process of the pirn winder machine which functions to wind yarn raw materials according to the desired weight and according to the available TFO capacity (700 gr, 714 gr, 1000gr or 1500gr). However, regardless of production quality standards on the pirn winder machine, it does not rule out the possibility that defects will always occur. Therefore it is necessary to have quality control in the production process of this pirn winder machine. Its function is clear to reduce the number of defects and improve the quality of production produced. Statistical Process Control (SPC) is a statistical analysis used for quality control, starting from monitoring, analyzing, predicting, controlling and improving the production process and product quality through control charts. Statistical quality control using SPC (Statistical Process Control) has seven statistical tools that can be used as tools to control quality, namely, check sheets, histograms, P control charts, pareto diagrams, cause and effect diagrams, scatter diagrams, and diagrams. process.